Barriers to early diagnosis of chronic kidney disease and use of sodium-glucose cotransporter-2 inhibitors for renal protection: A comprehensive review and call to action - Czupryniak, Leszek; Mosenzon, Ofri; Rychlík, Ivan; Clodi, Martin; Ebrahimi, Fahim; Janez, Andrej; Kempler, Peter; Małecki, Maciej; Moshkovich, Evgeny; Prázný, Martin; Sourij, Harald; Tankova, Tsvetalina; et al. (Diabetes, obesity & metabolism, 2024)
Chronic kidney disease (CKD) affects approximately 13% of people globally, including 20%-48% with type 2 diabetes (T2D), resulting in significant morbidity, mortality, and healthcare costs. There is an urgent need to increase early screening and intervention for CKD. We are experts in diabetology and nephrology in Central Europe and Israel. Herein, we review evidence supporting the use of sodium-glucose cotransporter-2 (SGLT2) inhibitors for kidney protection and discuss barriers to early CKD diagnosis and treatment, including in our respective countries. SGLT2 inhibitors exert cardiorenal protective effects, demonstrated in the renal outcomes trials (EMPA-KIDNEY, DAPA-CKD, CREDENCE) of empagliflozin, dapagliflozin, and canagliflozin in patients with CKD. EMPA-KIDNEY demonstrated cardiorenal efficacy across the broadest renal range, regardless of T2D status. Renoprotective evidence also comes from large real-world studies. International guidelines recommend first-line SGLT2 inhibitors for patients with T2D and estimated glomerular filtration rate (eGFR) ≥20 mL/min/1.73 m2, and that glucagon-like peptide-1 receptor agonists may also be administered if required for additional glucose control. Although these guidelines recommend at least annual eGFR and urine albumin-to-creatinine ratio screening for patients with T2D, observational studies suggest that only half are screened. Diagnosis is hampered by asymptomatic early CKD and under-recognition among patients with T2D and clinicians, including limited knowledge/use of guidelines and resources. Based on our experience and on the literature, we recommend robust screening programmes, potentially with albuminuria self-testing, and SGLT2 inhibitor reimbursement at general practitioner (GP) and specialist levels. High-tech tools (artificial intelligence, smartphone apps, etc.) are providing exciting opportunities to identify high-risk individuals, self-screen, detect abnormalities in images, and assist with prescribing and treatment adherence. Better education is also needed, alongside provision of concise guidelines, enabling GPs to identify who would benefit from early initiation of renoprotective therapy; although, regardless of current renal function, cardiorenal protection is provided by SGLT2 inhibitor therapy.
Keywords: glukosidy; empagliflozin; Humans; Sodium-Glucose Transporter 2 Inhibitors; časná diagnóza; chronic kidney disease; Benzhydryl Compounds; Glomerular Filtration Rate; type 2 diabetes; lidé; chronická renální insuficience; hodnoty glomerulární filtrace; Diabetes Mellitus, Type 2; SGLT2 inhibitor; Practice Guidelines as Topic; diabetické nefropatie; glifloziny; směrnice pro lékařskou praxi jako téma; Early Diagnosis; Diabetic Nephropathies; Glucosides; benzhydrylové sloučeniny; renal protection; Renal Insufficiency, Chronic; diabetes mellitus 2. typu; dapagliflozin